Evaluation of left ventricular dimension and systolic function by standard transthoracic echocardiography before and 24-hours after percutaneous closure of patent ductus arteriosus in 120 dogs. - Diego Piantedosi; Alfonso Piscitelli; Angela De Rosa; Blanca Serrano Lopez; Marta Claretti; Elisabetta Boz; Laura Mazzoni; Iolanda Navalon Calvo; Paolo Ciaramella; Claudio Bussadori (PLoS ONE, 2019)
One hundred and twenty dogs were enrolled to value the effect of loading condition changes on left ventricular volumes before and 24-hours after the patent ductus arteriosus (PDA) occlusion by Amplatzer Canine Duct Occluder (ACDO) using standard echocardiography. The animals were divided in pure breed (n. 94) and mixed breed (n. 26); subsequently, the pure breed dogs were divided on the basis of the size of the breed of belonging in 3 groups (small size n. 36; medium size n. 8; large size n. 50). Moreover, the animals were divided in three classes based on their age: until 6 months; 6-12 months; over 12 months. A significant reduction of all the examined parameters (left ventricle internal diameter at end-diastole-LVIDd; left ventricle internal diameter at end-systole-LVIDs; end-diastolic volume-EDV; end-systolic volume-ESV; end-diastolic volume index-EDVI; end-systolic volume index-ESVI; fractional shortening-FS) was observed after ductal closure. Twenty-four hours after the closure, the evaluation of the relative percentage difference (RPD) of the echocardiographic parameters showed a significant reduction, higher in small size breed than in large size breed dogs. No significant difference related to breed size was observed only for RPD_FS variable. A significant interaction effect, between breed size and age classes, was observed only for RPD_EDVI (F = 3.39; p = 0.039). Until six months of age there was no significant difference in RPD_EDVI reduction, but over 6 months a significant reduction between small size and large size breed dogs at 24-hours from the occlusion was observed. In conclusion, our data seem to indicate that small breed dogs show a greater tolerance to congenital volume overload than large breed dogs, and this finding could be justify a delay of PDA closure in order to simplify the interventional procedure.